Assisted peritoneal dialysis across Europe: Practice variation and factors associated with availability. Issue 6 (November 2021) - van Eck van der Sluijs, Anita; van Jaarsveld, Brigit C; Allen, Jennifer; Altabas, Karmela; Béchade, Clémence; Bonenkamp, Anna A; Burkhalter, Felix; Clause, Anne-Lorraine; Corbett, Richard W; Dekker, Friedo W; Eden, Gabriele; François, Karlien; et al.
Background: In Europe, the number of elderly end-stage kidney disease patients is increasing. Few of those patients receive peritoneal dialysis (PD), as many cannot perform PD autonomously. Assisted PD programmes are available in most European countries, but the percentage of patients receiving assisted PD varies considerably. Hence, we assessed which factors are associated with the availability of an assisted PD programme at a centre level and whether the availability of this programme is associated with proportion of home dialysis patients. Methods: An online survey was sent to healthcare professionals of European nephrology units. After selecting one respondent per centre, the associations were explored by χ 2 tests and (ordinal) logistic regression. Results: In total, 609 respondents completed the survey. Subsequently, 288 respondents from individual centres were identified; 58% worked in a centre with an assisted PD programme. Factors associated with availability of an assisted PD programme were Western European and Scandinavian countries (OR: 5.73; 95% CI: 3.07–10.68), non-academic centres (OR: 2.01; 95% CI: 1.09–3.72) and centres with a dedicated team for education (OR: 2.87; 95% CI: 1.35–6.11). Most Eastern & Central European respondents reported that the proportion of incident and prevalent home dialysis patients was <10% (72% and 63%), while 27% of Scandinavian respondents reported a proportion of >30% for both incident and prevalent home dialysis patients. Availability of an assisted PD programme was associated with a higher incidence (cumulative OR: 1.91; 95% CI: 1.21–3.01) and prevalence (cumulative OR: 2.81; 95% CI: 1.76–4.47) of patients on home dialysis. Conclusions: Assisted PD was more commonly offered among non-academic centres with a dedicated team for education across Europe, especially among Western European and Scandinavian countries where higher incidence and prevalence of home dialysis patients was reported.